Characterization of Volatile Organic Compounds at a Heavy-Traffic Site in Daegu, South Korea - Seo, Young-Kyo; Narayana Suvarapu, Lakshmi; Baek, Sung-Ok (Asian Journal of Chemistry, 2012)
This paper reports the monitoring results for a wide range of volatile organic compounds at a heavy traffic site in Daegu city, South Korea during the spring, summer and fall of 2010. Seasonal and diurnal variations were examined to understand the variability of the volatile organic compound concentrations with time. Correlation analysis revealed the effect of meteorological conditions on the measured levels of volatile organic compounds. Advanced statistical methods, such as principle component analysis and pollution rose analysis, were applied to understand the sources and behaviour of volatile organic compounds at this particular site. The ambient levels of volatile organic compounds measured in this study were compared with the results obtained in 2000 at the same sampling site. This comparative study showed that most of the volatile organic compound concentrations were reduced considerably (by -70 %) compared to those 10 years ago due to intensive governmental programs to reduce volatile organic compound emissions over the last 10 years. The BTEX concentrations reported at traffic related sites in other Korean and Asian cities were compared with the data obtained in the present study. The BTEX concentration ratios of the present study were approximately 0.7:10.9:1:1.8. The concentration of benzene measured at the present site was lower than that in other traffic related sites in Korea and Asian cities. The health implications for the benzene levels measured from this study are also discussed.